The variations of electron density and temperature related to seismic activities observed by CSES - Keying Zhu; Lin Zheng; Rui Yan; Xuhui Shen; Zhima Zeren; Song Xu; Wei Chu; Dapeng Liu; Na Zhou; Feng Guo (Natural Hazards Research, 2021)
Abstracts: In this study, we present the variations of electron density (Ne) and electron temperature (Te) in the nighttime ionosphere above the areas of seismic activities by the statistical method. The Ne and Te were observed by the CSES over ~2.5 years from May 2018 to December 2020. In the statistical analysis, the Ne and Te closed to the epicenters both in space and time are compared with their background values. The data associated with aftershocks, at high latitudes, and during high magnetic activity periods are carefully checked and finally removed from the statistics, to avoid spurious effects and the high variability of the ionosphere on the statistics. The results show that: (1) During nighttime, anomalous ionospheric perturbations related to earthquakes with magnitudes larger than 5 are in evidence; (2) According to the histogram distributions of Ne and Te perturbations, the positive variations of Ne and the negative variations of Te are related to seismic activities; (3)The significant variations of positive Ne and negative Te related to earthquakes mainly occurred ~1–7 days and ~13–15 days before the earthquakes respectively, and within 200 ​km from the epicenters.